Identification of Neuroendocrine Stress Response-Related Circulating MicroRNAs as Biomarkers for Type 2 Diabetes Mellitus and Insulin Resistance - Liang, Ying-Zhi; Dong, Jing; Zhang, Jie; Wang, Shuo; He, Yan; Yan, Yu-Xiang (Frontiers in Endocrinology, 2018)
Background: Chronic stress plays an important role in the development of type 2 diabetes mellitus (T2DM) and insulin resistance (IR). MicroRNAs (miRNAs) play key roles in mediating stress responses by regulating the expression of target genes. This study systematically screened and identified the neuroendocrine stress response related circulating miRNAs which associated with T2DM and IR. Methods: Based on the differential plasma expression profiles between individuals with and without T2DM, stress related miRNAs were selected from those differently expressed miRNAs whose targets are involved in known neuroendocrine pathway of stress response. Candidate miRNAs were further validated by qRT-PCR in a large sample including 112 T2DM patients, 72 individuals with impaired fasting glucose (IFG) and 94 healthy controls. The association between miRNA expression and potential risk of T2DM and IFG was assessed by multivariate logistic regression models. The miRNA predictors of IR were identified by stepwise multiple regression analysis. The diagnostic performance for T2DM was evaluate by area under the receiver operating characteristic curve (AUC). Results: Let-7b, let-7i, miR-142, miR-144, miR-155 and miR-29a were selected as candidate miRNAs for validation. Increased expression of let-7b, miR-144 and miR-29a and decreased expression of miR-142 were significant independent predictors of T2DM, IFG and IR (P<0.0125). These miRNAs significantly correlated with stress hormone levels (P<0.0125). A three-miRNA panel including let-7b, miR-142 and miR-144 had a high accuracy for diagnosing T2DM (AUC=0.871, 95% CI: 0.722–0.919). Conclusion: Let-7b, miR-142, miR-144, and miR-29a in plasma may be important markers of neuroendocrine stress response and may play a role in the pathogenesis of T2DM and IR.